PERSIAN ARCHITECTURE: A SOURCE OF INSPIRATION FOR MUGHAL IMPERIAL MOSQUES IN NORTH INDIA - Mohammad Saquib; Asif Ali (Journal of Islamic Architecture, 2023)
India and Persia have had a strong socio-cultural relationship since the ancient period. There had been a cultural link between the two countries. Indo-Persian cultural amalgamation had increased with the advent of Islam in the Indian subcontinent. The syncretism of these two cultures influenced all aspects of life, including literature, art and architecture. This paper discusses the influence of Persian architecture on Mughal imperial mosques in North India. A review of literature from various scholars on possible influencing factors is presented, accompanied by an observation-based analysis of the architectural features of Persian mosques. Subsequently, the paper identifies and examines various Persian architectural elements existing in Mughal mosques in India. The results indicate that Persian architecture significantly influenced Mughal mosques in North India and using locally available materials made these mosques unique in their architectural styles.